(untitled) - Ukens, Lorraine L. (Hoboken, N.J., 2007)
101 Ways to Improve Customer Service provides a variety of training and development interventions that can be put to use right now with frontline service employees. Your customer service representatives directly influence the perception that customers have of your products and services and ultimately your company. It is vital that your employees develop service strategies to create a positive image, communicate effectively, and build customer rapport to support the underlying values and beliefs of your organization.
Keywords: Customer services,Employees; Training of